Sociology And Religion: Interaction, Conflict and Social Change In Society From Hadith Perspective - Rohman, Oo Abdul; Mahir, Mahir; Soleh, Yasin Mohamad; Ibn Ziyad, Muhammad Thoriq; Sholihuddin, Sholihuddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Religion and sociology are two fields that are inherently linked to human social life. Religion is an integral part of the lives of many individuals and societies around the world, influencing actions, values, norms and social structures. On the other hand, sociology is the study of social interaction, social institutions and social change in society. Both influence each other and form complex social dynamics. The purpose of this study is to investigate the interaction between religion and sociology, with a focus on conflict and social change, and how hadith views these matters. The research aims to provide deeper insights into how religion influences the social structure, norms and values of society and how sociology can be used as an approach to understanding religion as a social phenomenon. In addition, the research will also explore the impact of religious conflict in society and the role of religion in the social changes that take place. What is important from the findings of this research is that the sociology of religion will provide knowledge about the patterns of religious social interaction in society and how they build structures and infrastructure in religion. With the sociology of religion, one will find a scientifically standardized pattern or concept of how religious people build a social system that respects each other and upholds tolerance. As a result, by studying the sociology of religion one will be able to personally control social actions in religion as well as control oneself. It is also confirmed by the hadith of the Prophet Muhammad Saw that religious life, especially a Muslim, must uphold science, tolerance, and patterns of social life must rely on religion, especially in Islam everything has been regulated and can be implemented.